2007
DOI: 10.1017/s1751731107000195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary incorporation of different antioxidant extracts and free-range rearing on fatty acid composition and lipid oxidation of Iberian pig meat

Abstract: This investigation was designed to evaluate the effects of feeding either free range or in confinement using concentrated diets with the same ingredients and oil source (5.5% of olive oleins) but with different antioxidant supplementation [control diet with a basal level of a-tocopheryl acetate (control); 200 mg/kg synthetic all-rac-a-tocopheryl acetate (E all-rac ); 200 mg/kg natural RRR-a-tocopheryl-acetate (E RRR-); flavonoid extract-enriched diet (A Flav ); and phenolic compound-enriched extract (A Phen )]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 35 publications
2
17
2
Order By: Relevance
“…Previous papers have shown either a higher marbling of Iberian hams from pigs fattened on acorn and grass than in those from pigs fed on concentrates (González & Tejeda, 2007) or similar values (Ventanas, Ventanas, & Ruiz, 2007), mainly due to the higher IMF content of the formers, which has been shown as the main factor determining the marbling degree (Muriel, Ruiz, Martin, Petrón, & Antequera, 2004;Ruiz-Carrascal et al, 2000). In the present study, hams from Iberian pigs fed HO diets showed higher marbling scores than AG ones.…”
Section: Agsupporting
confidence: 53%
“…Previous papers have shown either a higher marbling of Iberian hams from pigs fattened on acorn and grass than in those from pigs fed on concentrates (González & Tejeda, 2007) or similar values (Ventanas, Ventanas, & Ruiz, 2007), mainly due to the higher IMF content of the formers, which has been shown as the main factor determining the marbling degree (Muriel, Ruiz, Martin, Petrón, & Antequera, 2004;Ruiz-Carrascal et al, 2000). In the present study, hams from Iberian pigs fed HO diets showed higher marbling scores than AG ones.…”
Section: Agsupporting
confidence: 53%
“…The score plot of GC measurements illustrates that the CONJUGATED LINOLEIC ACID samples are clearly separated from ADDITIONAL ANTIOXIDANTS and CONTROL samples along the first PC. The fatty acid profiles of samples from CONTROL and ADDITIONAL ANTIOXIDANTS dietary treatments were similar since the flavonoids present in the ADDITIONAL ANTIOXIDANTS diet did not interfere significantly on the fatty acid composition of subcutaneous fat (Gonzalez & Tejeda, 2007). The samples from animals fed CONJUGATED LINOLEIC ACID showed a higher percentage of saturated and polyunsaturated fatty acids and a lower percentage of monounsaturated fatty acids compared with the other two diets ( Table 2).…”
Section: Nir Spectra Analysismentioning
confidence: 85%
“…For instance, the level of linolenic (C18:3) and other n-3 PUFA is highly increased, and the n-6 : n-3 ratio is decreased in meat from pigs reared on pasture compared with controls, as a consequence of the very high amount of C18:3 in the grass (Nilzen et al, 2001;Bee et al, 2004;Lebret and Guillard, 2005). The higher n-3 PUFA is accompanied by an increased vitamin E (a-and g-tocopherols) deposition in both external fat and intramuscular lipids, thus preventing further excessive lipid oxidation and development of thiobarbituric acid-reactive substances (TBARS) during meat storage (Andres et al, 2001;Nilzen et al, 2001;Gonzá lez and Tejeda, 2007). Therefore, outdoor rearing beneficially modifies the nutritional quality of meat.…”
Section: Rearing Systemsmentioning
confidence: 99%
“…The high proportions of starch and fat in the acorns lead to a very high accumulation of body lipids, whereas the grass supply is an important source of protein and fibre and compensates for the low protein concentration of acorns. Moreover, the high proportions of C18:1n-9 linoleic in acorns and n-3 fatty acid in grass modify the back fat and IMF composition towards increased proportions of C18:1n-9 and long-chain n-3 PUFA, and decreased proportions of SFA and linoleic (C18:2n-6) fatty acid (Rey et al, 2006;Gonzá lez and Tejeda, 2007;Ventanas et al, 2007b). As mentioned above, grass is also an important source of both a-tocopherol and the more specific g-tocopherol, which prevents subsequent lipid oxidation during storage, together with the other micronutrients ingested by the pigs during extensive finishing (Rey et al, 1997;Andres et al, 2001;Ventanas et al, 2008).…”
Section: Rearing Systemsmentioning
confidence: 99%